1969
DOI: 10.1042/bj1120343
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise cleavage of rabbit immunoglobin G by papain and isolation of four types of biologically active Fc fragments

Abstract: Four types of Fc fragments of different sizes were isolated by papain treatment of rabbit immunoglobulin G under various conditions and by subsequent chromatographic procedures. 1. Brief digestion at neutral pH without reduction produced a molecule in which the Fab and Fc fragments were still linked by a pair of labile disulphide bridges, and the Fc fragment released by cleaving these bonds, called 1Fc fragment, contained a portion of the ;hinge' region including an interchain disulphide bridge. Both complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…The quantitative reactivity of the serum with F(acb)z which possesses Cy2 but lacks Cy3 and its failure to react with Fab and the C,3 fragment indicated that RF possessed a restricted specificity to the Cy2 domain. The reactivity with mFc which lacks the hinge region [18] was decreased as compared to that with 1Fc carrying this region. Similar results were obtained by analysis of 25 individual sera from mice stimulated with IgG-TNP-LPS.…”
Section: Binding Specificity Of Rf Induced By Igg-tnp-lpsmentioning
confidence: 90%
See 1 more Smart Citation
“…The quantitative reactivity of the serum with F(acb)z which possesses Cy2 but lacks Cy3 and its failure to react with Fab and the C,3 fragment indicated that RF possessed a restricted specificity to the Cy2 domain. The reactivity with mFc which lacks the hinge region [18] was decreased as compared to that with 1Fc carrying this region. Similar results were obtained by analysis of 25 individual sera from mice stimulated with IgG-TNP-LPS.…”
Section: Binding Specificity Of Rf Induced By Igg-tnp-lpsmentioning
confidence: 90%
“…The pepsinderived C,3 fragment (Pep-111') [17], papain-derived Fab, lFc, mFc [18], and plasmin-derived F(acb)z [19] from RIgG were prepared as described. Identification of mFc and 1Fc was made by their dissociability and non-dissociability, respectively, in polyacrylamide gel electrophoresis in 0.1% SDS.…”
Section: Ligands and Antibody Reagents For Rf Assaymentioning
confidence: 99%
“…Non-covalently linked fragments consisting of V L dimer ) and V L and V H (Hochman, Inbar & Givol, 1973) have been prepared. Dimeric fragments consisting of most of the C y 3 domain have also been reported (Turner & Bennich, 1968;Utsumi, 1969;Ellerson et al 1972). On the other hand, Percy & Dorrington (1974) found that a light chain, from which most of the V domain was deleted, had no tendency to dimerize.…”
Section: Oligosaccharide Sitesmentioning
confidence: 92%
“…This fact could be related to the finding of papain cleavage at more than one site. The analogous cleavage of immunoglobulins by papain yielding Fab and Fc products has been reported to occur at two sites in the hinge region of most immunoglobulins (34,35).…”
Section: Assay Of Hl-mentioning
confidence: 99%